ON THE METHOD OF OBTAINING BORATELIC SUPERPHOSPHATE - Zhanyl DZHANMULDAYEVA; Galina SEITMAGZIMOVA; Aigul JANMULDAYEVA; Amid MURATOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Under laboratory conditions, the effect of the amount of borate salt additive, norm and temperature of EPA on the yield and quality of the product was studied. The effect of the ratio of phosphorite: borate salt on the degree of decomposition of phosphorite, the effect of the norm and temperature of extraction phosphoric acid on the degree of decomposition of the mixture of phosphorite: borate salt was also studied. On the basis of the obtained research results, the optimal parameters of the technological process for the production of borate-double superphosphate using borate salts of the Inderskoe field are determined.